Religionsfilosofi efter metafysik? - Grøn, Arne (Dansk teologisk tidsskrift, 2009)
Resumé In his book Transformationen Gottes Vagn Andersen pursues a double strategy. First, he interprets Jürgen Habermas’ post-metaphysical theory of communicative action as a last, secularized transformation of the idea of the absolute. More specifically, he argues that Habermas’ theory combines two ways of reformulating this idea, a Hegelian and a Kierkegaardian one. This leaves us with a tension between a notion of history as a whole and a notion of human finitude. Second, Vagn Andersen addresses the question: given our modern condition as reflected in Habermas’ theory, how is philosophy of religion possible? His answer draws upon a Kierkegaardian notion of the paradox leaving us with an unresolved tension between autonomy and heteronomy. This article discusses the approach and key issues in Vagn Andersen’s book, such as the question of metaphysics, the concepts of transcendence and immanence, the relation between normativity, temporality, and dialogue, and the question of rationality and religion.